Exploration and characterization of lipid-degrading bacteria from palm oil mill effluent - P. Periadnadi; N. Nurmiati; F.W. Siregar; T.W. Edelwis (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Lipid-degrading bacteria found in processing ponds of palm oil mill effluent are recognized for the capacity to break down lipid using lipase enzyme. Identifying novel strains of these bacteria with high bioremediation potential contributes valuable insights to the sustainable management of palm oil mill effluent. Therefore, this study aimed to identify potential bacteria, assess the in vitro lipid-degrading capabilities, characterize the traits, and evaluate lipid degradation activity of potential isolates from palm oil industry wastewater.METHODS: The method used for exploring the potential of lipid-degrading bacteria in palm oil mill effluent entailed a survey comprising various stages including detection of bacteria presence, in vitro assessment of potential indices, characterization, lipid degradation testing, and determination of lipase activity.FINDINGS: The results showed that several bacteria groups were present in palm oil mill effluent, including 50-74 percent lipolytic, 31-90 percent fermentative, 76-83 percent proteolytic, and 51-74 percent cellulolytic. Selected lipid-degrading isolates demonstrated significant in vitro potential, as evidenced by high lipolytic and fermentative indices. Isolate Enzymatic 3 had the highest lipolytic index, degradation value (48.72 percent), and lipase activity (0.12 units/milliliter), identified as Bacillus cereus central carbon metabolism 2010. Similarly, isolate Fermentative 2 was found to have the highest fermentative index, degradation value (22.35 percent), and lipase activity (0.01 units/milliliter), identified as Bacillus thuringiensis American type culture collection 10792.CONCLUSION: Based on the results, isolates Enzymatic 3 and Fermentative 2 showed promising potential as biological agents for bioremediation of palm oil mill effluent. The results underscored the promising potential of specific bacteria isolates in mitigating lipid-rich effluents, advocating for the integration into sustainable wastewater management practices in palm oil industry. This study provided valuable insights for future investigations aimed at unraveling the intricate mechanisms governing lipid degradation and fostering environmentally friendly solutions for industrial waste management.